2021
DOI: 10.1038/s41398-020-01159-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology associated with altered synaptic transcriptome in the dorsolateral prefrontal cortex of depressed subjects

Abstract: Disrupted synaptic plasticity is the hallmark of major depressive disorder (MDD), with accompanying changes at the molecular and cellular levels. Often, the maladaptive molecular changes at the synapse are the result of global transcriptional reprogramming dictated by activity-dependent synaptic modulation. Thus far, no study has directly studied the transcriptome-wide expression changes locally at the synapse in MDD brain. Here, we have examined altered synaptic transcriptomics and their functional relevance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 84 publications
2
8
0
Order By: Relevance
“…Our results are functionally relevant MDD-associated impaired synaptic plasticity involving dynamic changes in gene regulatory networks ( Bristot et al, 2020 ; Yoshino et al, 2021b ). These dynamic changes quickly respond to environmental stimuli ( Lopizzo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 51%
“…Our results are functionally relevant MDD-associated impaired synaptic plasticity involving dynamic changes in gene regulatory networks ( Bristot et al, 2020 ; Yoshino et al, 2021b ). These dynamic changes quickly respond to environmental stimuli ( Lopizzo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 51%
“…1–2 µg total RNA from each sample was taken for RNA-seq library preparation following the method described previoulsy 24 . Briefly, mRNA was isolated from total RNA with NEBNext Poly(A) mRNA Magnetic Isolation Module.…”
Section: Methodsmentioning
confidence: 99%
“…Synaptic dysfunction played an important role in the pathogenesis and development of MDD. [51][52][53] Kang et al revealed the decrease in the expression of synaptic function related genes and the corresponding decrease in the number of synapses in dlPFC of MDD subjects. [53] Our results also show that the synaptic plasticity of SUS mice was defective, as indicated by the significant dysregulation of synaptic plasticity related genes (Arc, Cplx2, Syp, Nrgn, Pmch, Calb2, Syt4) in multiple brain regions in SUS mice (Table S4), which may be due to chronic maladjustment of stress response, loss of synaptic connection and impaired synaptogenesis in these brain regions.…”
Section:  Stress-induced Gene Dysregulation Associated With Synapti...mentioning
confidence: 99%